Germline mutations in the DNA damage response genes BRCA1, BRCA2, BARD1 and TP53 in patients with therapy related myeloid neoplasms. Issue 7 (31st May 2012) - Schulz, Eduard; Valentin, Angelika; Ulz, Peter; Beham-Schmid, Christine; Lind, Karin; Rupp, Verena; Lackner, Herwig; Wölfler, Albert; Zebisch, Armin; Olipitz, Werner; Geigl, Jochen; Berghold, Andrea; et al.
Abstract : Background: Therapy related myeloid neoplasms (t-MNs) are complex diseases originating from an interplay between exogenous toxicities and a susceptible organism. It has been hypothesised that in a subset of cases t-MNs develop in the context of hereditary cancer predisposition syndromes. Methods: The study systematically evaluated pedigrees of patients with t-MNs for cancer incidences and the possibility of a hereditary cancer predisposition syndrome. In addition, mutational analyses were performed using constitutional DNA from index patients, and deleterious heterozygous germline mutations were assessed for loss of heterozygosity in sorted leukaemic cells by single nucleotide polymorphism array. Results: A nuclear pedigree was obtained in 51/53 patients with t-MNs resulting in a total of 828 individuals analysed. With a standardised incidence ratio of 1.03 (95% CI 0.74 to 1.39), the tumour incidence of first- degree relatives was not increased. However, six pedigrees were suggestive for a hereditary breast and ovarian cancer syndrome, three of a Li-Fraumeni like syndrome, and three index patients showed multiple primary neoplasms. Mutational analysis revealed two BRCA1 (c.3112G→T, c.5251C→T), one BRCA2 (c.4027A→G), two BARD1 (C557S) and four TP53 germline mutations (g.18508_18761delinsGCC, c.847C→T, c.845_848dupGGCG, c.1146delA) in nine of 53 (17%) index patients with t-MNs. Loss of heterozygosity in leukaemic cells was demonstrated for the BRCA1 c.3112G→T and TP53 c.845_848dupGGCG mutations, respectively. Conclusion: It is concluded that a proportion of patients with t-MNs carry cancer susceptibility mutations which are likely to contribute to therapy related leukaemogenesis.